Characterisation of magnesium, zinc and iron sulphates for thermochemical storage. Issue 4 (29th October 2019) - Rehman, Ata Ur; Hayat, Asif; Munis, Adnan; Zhao, Tianyu; Israr, Muhammad; Maosheng, Zheng
Abstract : Thermochemical heat storage materials such as magnesium, zinc and iron sulphates offer high energy storage densities and a clean means of long-term solar-energy storage. In this study, the dynamic properties of these three salts were investigated based on their hydration and dehydration characteristics. To investigate the effect of regeneration temperatures on the materials' physio-chemical properties, four sets of temperatures were used. At 100 °C, zinc sulphate showed a significant loss of water as compared to the magnesium and iron salts, while in the hydration process at lower temperatures, zinc sulphate showed the highest sorption enthalpy and energy density. Furthermore, the crystallinity of salt hydrates were characterised using powder X-ray diffraction measurements, which revealed that dehydration of water molecules occurred only in magnesium sulphate, whereas partial distortion occurred in iron sulphate with a rising temperature. Taking all the results together indicated that zinc sulphate is more energy-efficient than both magnesium and iron sulphate. With a calculated hydration energy density at 100 °C of 1.26 GJ/m 3, zinc sulphate is the best option of the three salts for use as a thermochemical material.